Global existence to the initial–boundary value problem for a system of semilinear wave equations. (November 2016) - Nakao, Mitsuhiro
Abstract: We prove the global existence of finite energy and H 2 solutions for a system of nonlinear wave equations in a bounded domain. One equation of the system has a dissipative term, while another equation has no dissipative mechanism. To derive the delicate a priori estimates we employ a 'loan' method.